PENINGKATAN PEMAHAMAN MATEMATIKA TENTANG KONSEP LUAS BANGUN DATAR MELALUI PERMAINAN ENGKLEK DI KELAS 5 SDN SERTAJAYA 05 (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine students' level of understanding of the concept of flat shapes through the application of interactive mathematics learning that utilizes the traditional game of Engklek. This study uses a quantitative approach with a quasi-experimental design in the form of a one-group pretest-posttest. The research subjects were fifth-grade students at SDN Sertajaya 05, located in Sertajaya Village, East Cikarang District. This research design was used to measure the effectiveness of learning interventions in improving students' understanding of the concept of calculating the area of flat shapes through contextual learning that relates mathematical material to students' real experiences. Problems found in the field included low student understanding of the concept of area and difficulty in applying mathematical formulas to everyday problems. A total of 30 students were involved as research respondents. Data collection techniques included observation, testing, and documentation. The results of data analysis showed that the use of the traditional Engklek game in mathematics learning significantly improved the understanding of the concept of flat shape area in fifth-grade students at SDN Sertajaya 05. In addition, the results of observations showed an increase in student enthusiasm and involvement during the learning process. Learning based on traditional games helped students understand mathematical concepts more concretely and meaningfully, making learning more effective and meaningful.